Genetic diversity of the genus Terfezia (Pezizaceae, Pezizales): New species and new record from North Africa - Zitouni-Haouar, Fatima El-Houaria; Carlavilla, Juan Ramón; Moreno, Gabriel; Manjón, José Luis; Fortas, Zohra (Phytotaxa, 2018)
Morphological and phylogenetic analyses of large ribosomal subunit (28S rDNA) and internal transcribed spacer (ITS rDNA) of Terfezia samples collected from several bioclimatic zones in Algeria and Spain revealed the presence of six distinct Terfezia species: T. arenaria, T. boudieri, T. claveryi; T. eliocrocae (reported here for the first time from North Africa), T. olbiensis, and a new species, T. crassiverrucosa sp. nov., proposed and described here, characterized by its phylogenetic position and unique combination of morphological characters. A discussion on the unresolved problems in the taxonomy of the spiny-spored Terfezia species is conducted after the present results.